Searching for America's heart : - Edelman, Peter (Houghton Mifflin, 2001)
Peter Edelman has worked as an aide to Robert F. Kennedy, a lawyer, a children's advocate, and a policymaker. He has devoted his life to the cause of justice and to ending inequality. But in 1996, while serving in the Clinton administration as an expert on welfare policy and children, he found himself in an untenable position. The president signed a new welfare bill that ended a sixty-year federal commitment to poor children, and as justification invoked the words of RFK. For Edelman, Clinton's twisting of Kennedy's vision was deeply cynical, so in a rare gesture that sparked front-page coverage in the New York Times and the Washington Post, he resigned from the administration. The nation, he believed, had been harmed. Drawing on Edelman's vast personal experience with the issues and many of the key figures, SEARCHING FOR AMERICA'S HEART shows that in an age of unprecedented prosperity, Americans have in many respects forsaken their fellow citizens. While we daily break economic records, we have largely given up our vision of social and economic justice, leaving behind a devastatingly large number of poor and near-poor, many of them children. Edelman shines a bright light on these forgotten Americans. Also, based in part on a firsthand look at community efforts across the country, he proposes a bold and practical program for addressing the difficult issues of entrenched poverty. Edelman focuses on novel ways of braiding together national and local civic activism, reinvigorating our commitment to children, and building hope in our most shattered communities. Surveying the American landscape at the beginning a new presidency and a new Congress, SEARCHING FOR AMERICA'S HEART lays the foundation for a newly conceived politics, a vision true to the legacy of Robert F. Kennedy.